A comprehensive nanopore sequencing methodology deciphers the complete transcriptional landscape of cyclin‐dependent kinase 4 (CDK4) in human malignancies. (4th October 2021) - Adamopoulos, Panagiotis G.; Athanasopoulou, Konstantina; Tsiakanikas, Panagiotis; Scorilas, Andreas
Abstract : Cyclin‐dependent kinase 4 (CDK4) is a member of the cyclin‐dependent kinases, a family of protein kinases with outstanding roles in signaling pathways, transcription regulation, and cell division. Defective or overactivated CDK4/cyclin D1 pathway leads to enhanced cellular proliferation, thus being implicated in human cancers. Although the biological role of CDK4 has been extensively studied, its pre‐mRNA processing mechanism under normal or pathological conditions is neglected. Thus, the identification of novel CDK4 mRNA transcripts, especially protein‐coding ones, could lead to the identification of new diagnostic and/or prognostic biomarkers or new therapeutic targets. In the present study, instead of using the 'gold standard' direct RNA sequencing application, we designed and employed a targeted nanopore sequencing approach, which offers higher sequencing depth and enables the thorough investigation of new mRNAs of any target gene. Our study elucidates for the first time the complex transcriptional landscape of the human CDK4 gene, highlighting the existence of previously unknown CDK4 transcripts with new alternative splicing events and protein‐coding capacities. The relative expression levels of each novel CDK4 transcript in human malignancies were elucidated with custom qPCR‐based assays. The presented wide spectrum of CDK4 transcripts ( CDK4 v.2–v.42) is only the first step to distinguish and assemble the missing pieces regarding the exact functions and implications of this fundamental kinase in cellular homeostasis and pathophysiology. Abstract : In the present study, we designed and employed a targeted nanopore sequencing approach, aiming to identify novel mRNA transcripts of the human CDK4 gene. Our study elucidates for the first time the complex transcriptional landscape CDK4, highlighting the existence of previously unknown CDK4 transcripts with new alternative splicing events and protein‐coding capacities. The relative expression levels of each novel CDK4 transcript in human malignancies were elucidated with custom qPCR‐based assays.